Non-Canonical WNT5A Signaling Through RYK Contributes to Aggressive Phenotype of the Rheumatoid Fibroblast-Like Synoviocytes - Rodriguez-Trillo, Angela; Mosquera, Nerea; Pena, Carmen; Rivas-Tobío, Fatima; Mera-Varela, Antonio; Gonzalez, Antonio; Conde, Carmen (Frontiers in Immunology, 2020)
Abstract We hypothesized that WNT5A could contribute to the enhanced migration and invasiveness of rheumatoid arthritis fibroblast-like synoviocytes (RA FLS), which is one of the incompletely understood aspects of the RA FLS aggressive phenotype. This hypothesis is based on the previous evidence of a WNT5A role in both, RA and cell migration. Migration and invasion of RA FLS were assessed after incubation with recombinant Wnt5a (rWnt5a) or silencing of the endogenous WNT5A expression. The expression of WNT5A, WNT receptors, cytokines, chemokines and metalloproteinases was quantified with RT-PCR. The WNT pathway was explored with gene silencing, antibody and pharmacological inhibition followed by migration assays and phosphoprotein western blots. Here, we reported that rWnt5a promoted migration and invasion of RA FLS, whereas knockdown of the endogenous WNT5A reduced them. These effects were specific to the RA FLS since they were not observed in FLS from osteoarthritis (OA) patients. Also, rWnt5a induced the expression of IL6, IL8, CCL2, CXCL5, MMP1, MMP3, MMP9 and MMP13 from baseline or potentiating the TNF induction, WNT5A signaling required the RYK receptor and was mediated through the WNT/Ca2+ and the ROCK pathway. These pathways involved the RYK and ROCK dependent activation of the p38, ERK, AKT and GSK3β kinases, but not the activation of JNK. Together these findings indicate that WNT5A contributes to the enhanced migration and invasiveness of RA FLS through RYK and the specific activation of ROCK and downstream kinases.